2019
DOI: 10.1016/j.ejrad.2018.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of diffusion-weighted MRI of the prostate using whole lesion ADC values, skew and histogram analysis

Abstract: To investigate the repeatability of diffusion-weighted imaging parameter including ADC-derived histogram values in prostate cancer. Methods: 10 patients with prostate cancer were prospectively recruited to a retest cohort. 3 T diffusion-weighted MRI of the prostate was acquired consecutively with patient getting off the scanner between studies. Prostatectomy-histopathology defined tumour regions-of-interest were outlined on ADC maps and diffusionweighted metrics including histograms were calculated. The coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 36 publications
5
22
0
Order By: Relevance
“…In this study the patient number was too small to permit reliable hypothesis testing of the multiple parameters that would be produced by histogram or textural analysis. Future work with a larger number of patients could however extend this study to assess intervoxel heterogeneity of water movement by using histogram analysis 35,36 or Haralick textural features 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study the patient number was too small to permit reliable hypothesis testing of the multiple parameters that would be produced by histogram or textural analysis. Future work with a larger number of patients could however extend this study to assess intervoxel heterogeneity of water movement by using histogram analysis 35,36 or Haralick textural features 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The coefficient of variation between the coils was only 12%, which is comparable to the repeatability and reproducibility error of around 10% reported for ADC measurements of restricted diffusion, used routinely in clinical MRI assessment of the prostate. [32][33][34] There was one notable outlier (Patient 6) with a PZ tumor with a TSC value of 38.5 mM measured with the 23 Na coil, compared with 58.9 mM with the 13 C coil; this tumor was a small (volume 0.79 cm 3 ), peripherally located tumor and the discrepancy in the findings may have related to partial voluming effects.…”
Section: Discussionmentioning
confidence: 99%
“…The total number of patients assessed was relatively small. 32,33 TSC estimates will be affected by the SNR, which in turn is affected by the coil resonant frequency, and is accounted for in the quantitative measurements. Furthermore, the gyromagnetic ratio of the sample is not affected by the frequency of the coil, and so is not expected to directly affect the TSC estimates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Tristan Barrett et al. found that advanced measures of heterogeneity such as histogram skewness had poor repeatability (32). Their results may explain the limited diagnostic performance of skewness and kurtosis values in our study.…”
Section: Discussionmentioning
confidence: 99%